Autotaxin and LPA receptors represent potential molecular targets for the radiosensitization of murine glioma through effects on tumor vasculature. - Stephen M Schleicher; Dinesh K Thotala; Amanda G Linkous; Rong Hu; Kathleen M Leahy; Eugenia M Yazlovitskaya; Dennis E Hallahan (PLoS ONE, 2011)
Despite wide margins and high dose irradiation, unresectable malignant glioma (MG) is less responsive to radiation and is uniformly fatal. We previously found that cytosolic phospholipase A2 (cPLA(2)) is a molecular target for radiosensitizing cancer through the vascular endothelium. Autotaxin (ATX) and lysophosphatidic acid (LPA) receptors are downstream from cPLA(2) and highly expressed in MG. Using the ATX and LPA receptor inhibitor, α-bromomethylene phosphonate LPA (BrP-LPA), we studied ATX and LPA receptors as potential molecular targets for the radiosensitization of tumor vasculature in MG. Treatment of Human Umbilical Endothelial cells (HUVEC) and mouse brain microvascular cells bEND.3 with 5 µmol/L BrP-LPA and 3 Gy irradiation showed decreased clonogenic survival, tubule formation, and migration. Exogenous addition of LPA showed radioprotection that was abrogated in the presence of BrP-LPA. In co-culture experiments using bEND.3 and mouse GL-261 glioma cells, treatment with BrP-LPA reduced Akt phosphorylation in both irradiated cell lines and decreased survival and migration of irradiated GL-261 cells. Using siRNA to knock down LPA receptors LPA1, LPA2 or LPA3 in HUVEC, we demonstrated that knockdown of LPA2 but neither LPA1 nor LPA3 led to increased viability and proliferation. However, knockdown of LPA1 and LPA3 but not LPA2 resulted in complete abrogation of tubule formation implying that LPA1 and LPA3 on endothelial cells are likely targets of BrP-LPA radiosensitizing effect. Using heterotopic tumor models of GL-261, mice treated with BrP-LPA and irradiation showed a tumor growth delay of 6.8 days compared to mice treated with irradiation alone indicating that inhibition of ATX and LPA receptors may significantly improve malignant glioma response to radiation therapy. These findings identify ATX and LPA receptors as molecular targets for the development of radiosensitizers for MG.